'Dance to your daddy' - Lynda W.; Awre, Gabrielle (The University of Hull, 2017)
A conversation and sung lullaby. Lynda came to Hull from Derbyshire as a young teacher and had spent her working life in Hull also bringing up a family and working in schools with young children and special needs. She had some Geordie/North East origins in her family as described on the recording (her Grandma). She knew many of the traditional nursery rhymes and lullabies and was happy to sing them for me and talk about how she knew them. Lynda was in the Hull Freedom Chorus but these were recorded at her home. She was not long retired when the recording took place.